The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.18372/2411-6602.07.2230
|View full text |Cite
|
Sign up to set email alerts
|

Orbital evolution of 95Р/Chiron, 39P/Oterma, 29P/Shwassmann–Wachmann 1, and of 33 Centaurs

Abstract: нацiонального унiверситету iменi Тараса Шевченка В данiй роботi було проведено чисельне моделювання еволюцiї орбiт 34-х об'єктiв групи Кентаврiв i 2-х вiддалених комет групи Юпiтера-39Р/Отерма та 29Р/Швассмана-Вахмана 1 iз використанням метода Еверхарта. В результатi були отриманi еволюцiйнi треки елементiв орбiт 33-х Кентаврiв i 3-х комет (95Р/Хiрон, 29Р/Швассманна-Вахманна 1 i 39Р/Отерма) на 1 мiльйон рокiв в минуле та майбутнє. Проведено статистичний аналiз результатiв чисельного iнтегрування, виявленi трен… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…During the course of their evolution, studies have shown that at least one-third of the Centaurs will evolve onto cometary orbits with perihelia in the inner solar system Jewitt 2004;Bailey & Malhotra 2009). As such, the Centaurs are generally regarded as the principal parent population for the short period comets (Tiscareno & Malhotra 2003;Groussin et al 2004;Volk & Malhotra 2008;Bailey & Malhotra 2009;Jewitt 2009;Kovalenko et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…During the course of their evolution, studies have shown that at least one-third of the Centaurs will evolve onto cometary orbits with perihelia in the inner solar system Jewitt 2004;Bailey & Malhotra 2009). As such, the Centaurs are generally regarded as the principal parent population for the short period comets (Tiscareno & Malhotra 2003;Groussin et al 2004;Volk & Malhotra 2008;Bailey & Malhotra 2009;Jewitt 2009;Kovalenko et al 2011).…”
Section: Introductionmentioning
confidence: 99%